Coral disease distribution at Ras Mohammed and the Gulf of Aqaba, Red Sea, Egypt - MOHAMMED SHOKRY AHMED AMMAR; FEKRY ASHOUR; HODA ABDELAZIM (Nusantara Bioscience, 2013)
Abstract. Ammar MSA, Ashour F, Abdelazim H. 2013. Coral disease distribution at Ras Mohammed and the Gulf of Aqaba, Red Sea, Egypt. Nusantara Bioscience 5: 35-43. Six sites along the Gulf of Aqaba and Ras Mohammed, Red Sea, Egypt were studied for coral disease distribution relative to environmental stress. These sites are (i) South Taba, (ii) South Nuweiba, (iii) Canyon, (iv) Eel Garden (at Dahab), (v) Shark Observatory and (vi) Yolanda. Number of coral diseases ranges from 6 diseases at site 4 (Eeel Garden) to 12 diseases at site 3 (Canyon). The site having the lowest number of coral diseases (site 4) is characterized by the highest percentage cover of coral diseases (24%). The coral disease atramentous necrosis attained the highest percentage cover in all sites (5, 5, 6, 6, 2 and 3%) in sites 1-6 respectively. A total of 16 diseases were reported being distributed in the following order in sites 1-6: 9, 9, 12, 6, 8 and 7 respectively. The coral disease atramentous necrosis is the most widely distributed one being found in all 6 sites followed by dark spots disease and ulcerative white spots being reported in 5 sites. The disease that is least distributed is the white tips being reported in site 5 only. The most commonly distributed disease (atramentous necrosis) infected six corals in site 1, two corals in site 2, nine corals in site 3, two corals in site 4, five corals in site 5 and five corals in site 6. However, the least commonly distributed disease (white tips) infected only two corals (Acropora humilis and Millepora dichotoma). Site 1, having Cyphastrea serailia being infected with highest number of diseases is characterized by the maximum metal concentrations of Zn, Cd, Pb and Ni in water and highest metal concentrations for Cu, Zn and Pb in sediments. Site 2, having M. dichotoma being infected with the highest number of diseases, is characterized by the highest Cu concentration in water. Site 4, having fewer number of coral diseases and highest percentage disease cover attained the highest levels of Cd and Ni in sediments.